Picornavirus Modification of a Host mRNA Decay Protein - Rozovics, Janet M. (American Society of Microbiology, 2012)
Due to the limited coding capacity of picornavirus genomic RNAs, host RNA binding proteins play essential roles during viral translation and RNA replication. Here we describe experiments suggesting that AUF1, a host RNA binding protein involved in mRNA decay, plays a role in the infectious cycle of picornaviruses such as poliovirus and human rhinovirus. We observed cleavage of AUF1 during poliovirus or human rhinovirus infection, as well as interaction of this protein with the 5′ noncoding regions of these viral genomes. Additionally, the picornavirus proteinase 3CD, encoded by poliovirus or human rhinovirus genomic RNAs, was shown to cleave all four isoforms of recombinant AUF1 at a specific N-terminal site in vitro. Finally, endogenous AUF1 was found to relocalize from the nucleus to the cytoplasm in poliovirus-infected HeLa cells to sites adjacent to (but distinct from) putative viral RNA replication complexes.